VIOLATION OF COMMUNICATION RIGHTS AND FREE INTERNET ACCESS (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The present essay seeks to present the current conception of the so-called "communicative rights" from the context of human rights and their protection, which consents both internationally and internally. The study analyzes the extent and historical milestones of communicative rights, the issue of free access to the internet, the Marco Civil da Internet, the impasse of communication networks, and the legal issues regarding the realization of the "right to be forgotten". Thus, the work demands relevant aspects about how these rights are treated in the specialized doctrine and incident legislation as well as in the Brazilian jurisprudence and the Inter-American Court of Human Rights.